JURIDICAL REVIEW OF POLYGAMY PERFORMED BY CIVIL SERVANTS VIEWED FROM GOVERNMENT REGULATION NUMBER 45 OF 1990 (STUDY OF DECISION NUMBER 325/PDT.G/2019/PA.PWL) - Windi Destriyanti; Muhamad Gary Gagarin Akbar; Zarisnov Arafat (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2023)
Polygamy for civil servants is contained in Government Regulation Number 45 of 1990 amendment to Government Regulation Number 10 of 1983 concerning marriage and divorce permits for civil servants. The problems raised in this study are how to regulate polygamy carried out by civil servants based on Government Regulation Number 45 of 1990 concerning marriage and divorce permits for civil servants and how judges consider them in granting case requests number 325/Pdt.G/2019/PA. Pwl. The purpose of this study is to find out the polygamy arrangements carried out by civil servants based on Government Regulation Number 45 of 1990 concerning marriage and divorce permits for civil servants and judges' considerations in granting case requests number 325/Pdt.G/2019/PA.Pwl. This research is a type of qualitative research that uses a normative juridical approach, namely a research approach by researching and studying research objects through library research. As for the author's hypothesis that polygamy practiced by civil servants must be in accordance with the applicable laws and regulations, namely Government Regulation number 45 of 1990 concerning marriage and divorce permits for civil servants/ASN. As formulated in Article 4.